Oral D-methionine protects against cisplatin-induced hearing loss in humans: phase 2 randomized clinical trial in India. (1st August 2022) - Campbell, Kathleen C.; Rehemtulla, Alnawez; Sunkara, Prasad; Hamstra, Daniel; Buhnerkempe, Michael; Ross, Brian
Abstract: Objective: This exploratory Phase 2 clinical trial is the first determining safety and efficacy of oral D-methionine (D-met) in reducing cisplatin-induced ototoxicity. Design: Randomised parallel double-blind placebo-controlled exploratory Phase 2 study. Study samples: Fifty adult cancer patients received oral D-met or placebo before each cisplatin dose. Physical examination, blood collection and audiometry occurred at baseline and subsequent visits plus post-treatment audiometry. After attrition, final analysis included 27 patients. Results: Significant treatment group by ear and time (baseline vs. post-treatment) interactions occurred at 10 kHz and 11.2 kHz. Placebo and D-met groups differed in threshold shift for left ear at 11.2 kHz (mean difference = 22.97 dB [9.59, 36.35]). Averaging across ears, placebo group showed significant threshold shifts from baseline to post-treatment at 10 kHz (mean shift= −13.65 dB [−21.32, −5.98]), 11.2 kHz (−16.15 dB [−25.19, −7.12]), and 12.5 kHz (−11.46 dB [−19.18, −3.74]) but not 8 kHz (−8.65 dB [−17.86, 0.55]). The D-met group showed no significant threshold shifts (8 kHz: −1.25 dB [−7.75, 5.25]; 10 kHz:−3.93 dB [−8.89, 1.03]; 11.2 kHz:−4.82 dB [−11.21, 1.57]; 12.5 kHz:−3.68 dB [−11.57, 4.21]). Side effects did not significantly differ between groups. Conclusion: Oral D-met reduces cisplatin-induced ototoxicity in humans.